Bacterial leaf and fruit spot: A major constraint in pomegranate orchards (Indian Journal of Arid Horticulture, 2025)
Pomegranate (Punica granatum L.) belongs to the family Punicaceae. It has wider application in both. Ayurvedic and Unani traditional medicinal systems of medicine (Anonymous, 1989). Owing to different alkaloids particularly tannins, constituted in pomegranate leaves and fruits, there is no occurrence of much disease in this crop. But the leaf and fruit spots are the major diseases in humid regions of India, which indirectly affects the yield, and economic value of fruits in India. It is popularly known as oily spots in Maharastra area and nodal blight in Karnaraka. Ramesh et al. (1991) have reported that pomegranate bacterial blight appeared as an epidemic in Bangalore, Karnataka, India, causing 60-80% yield losses.